Revitalization of irsyad's da'wah: Transformation of Santri through riyadhah an-nafs - Nihayah, Ulin; Wibowo, Mungin Eddy; Sugiharto, Dwi Yuwono Puji; Formen, Ali (Jurnal Ilmu Dakwah, 2025)
Purpose – The purpose of this study was to examine the revitalization of Irsyad’s da’wah through the implementation of riyadhah an-nafs as a means of transforming the character and spirituality of santri in Islamic boarding schools Method – The population of this study consisted of santri from a modern Islamic boarding school in Indonesia. The study employed a qualitative approach, utilizing phenomenological methods. Data were collected through interviews, observations, and documentation. The data analysis employed thematic analysis to identify patterns of spiritual transformation. Result – The results showed that the practice of riyadhah an-nafs, including self-discipline, muhasabah, and spiritual exercises, significantly contributed to santri’s moral awareness, self-regulation, and da’wah orientation. These changes reinforced the essence of Irsyad’s da’wah as a guidance-based, transformative process. Implication – This method suggests that integrating Riyadhah an-nafs into pesantren curricula can effectively enhance the spiritual resilience and leadership capacity of santri in carrying out da'wah missions. Originality/Value – This study offers a novel integration between classical Islamic spiritual training and contemporary da’wah revitalization, emphasizing the role of inner transformation as a foundation for sustainable character development. *** Tujuan – Tujuan penelitian ini adalah untuk mengkaji revitalisasi da’wah Irsyad melalui penerapan riyadhah an-nafs sebagai sarana transformasi karakter dan spiritualitas santri di pesantren Islam. Metode – Populasi penelitian ini terdiri dari santri dari sebuah pesantren Islam modern di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologis. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Analisis data menggunakan analisis tematik untuk mengidentifikasi pola transformasi spiritual. Hasil – Hasil menunjukkan bahwa praktik riyadhah an-nafs, termasuk disiplin diri, muhasabah, dan latihan spiritual, secara signifikan berkontribusi pada kesadaran moral, pengaturan diri, dan orientasi dakwah santri. Perubahan ini memperkuat esensi dakwah Irsyad sebagai proses transformatif berbasis bimbingan. Implikasi – Metode ini menyarankan bahwa integrasi Riyadhah an-nafs ke dalam kurikulum pesantren dapat secara efektif meningkatkan ketahanan spiritual dan kapasitas kepemimpinan santri dalam melaksanakan misi da’wah. Orisinalitas/Nilai – Studi ini menawarkan integrasi baru antara pelatihan spiritual Islam klasik dan revitalisasi da’wah kontemporer, dengan menekankan peran transformasi batin sebagai landasan untuk pengembangan karakter yang berkelanjutan.